2011
DOI: 10.1007/s10142-011-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

PR-10, defensin and cold dehydrin genes are among those over expressed in Oxytropis (Fabaceae) species adapted to the arctic

Abstract: In many studied plants, typical responses to cold treatment include up-regulating the hydrophilic COR/LEA genes and down-regulating photosynthesis-related genes, carbohydrate metabolism, GDSL-motif lipase, hormone metabolism and oxidative regulation genes. However, next to nothing is known about gene expression in arctic plants, which are actually adapted to a harsh, cold environment. The molecular mechanisms behind the many specific adaptations of arctic plants, such as slow growth, well-developed root system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 71 publications
(102 reference statements)
1
39
0
Order By: Relevance
“…Moreover, PR-10 proteins are over expressed in Oxytopis (Fabaceae) species adapted to the Arctic as opposed to temperate species [92]. In a study by Vaas et al [93], overexpression of PR-10a in suspension cultures of Solanum tuberosum causes an enhanced osmotic tolerance, which in turn leads to enhanced ability for cryo preservation. Abiotic stress-induced Zea mays PR-10 genes (ZmPR-10 and ZmPR-10.1) were also up-regulated following infection with pathogenic bacteria Erwinia stewartii and fungus Aspergillus flavus in young maize leaves and immature kernels, respectively [9].…”
Section: Abiotic and Biotic Stresses: Pr-10 Responsementioning
confidence: 99%
“…Moreover, PR-10 proteins are over expressed in Oxytopis (Fabaceae) species adapted to the Arctic as opposed to temperate species [92]. In a study by Vaas et al [93], overexpression of PR-10a in suspension cultures of Solanum tuberosum causes an enhanced osmotic tolerance, which in turn leads to enhanced ability for cryo preservation. Abiotic stress-induced Zea mays PR-10 genes (ZmPR-10 and ZmPR-10.1) were also up-regulated following infection with pathogenic bacteria Erwinia stewartii and fungus Aspergillus flavus in young maize leaves and immature kernels, respectively [9].…”
Section: Abiotic and Biotic Stresses: Pr-10 Responsementioning
confidence: 99%
“…Nevertheless, arctic plants serve important purposes, such as feeding mammalian herbivores and insect pollinators. Using library subtraction and clone sequencing (ESTs), we recently reported that plantlets of two arctic Oxytropis species show a distinctive transcriptome compared to two temperate relative species (Archambault and Strömvik 2011). Arctic plantlets preferentially express response to stimulus (especially PR-10, cold dehydrins and defensin gene families) and ribosome biogenesis genes, whereas temperate plantlets express photosynthesis (including lhcbI and lhcaIII genes), ribosome biogenesis and translation and nucleosome assembly genes, as well as a few response to stimulus genes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that plantlet transcriptomes from temperate Oxytropis plantlets are mainly enriched in transcripts of the "Photosynthesis" category (Archambault and Strömvik 2011). Proteins of the light-harvesting complex, for instance LHCBI (also called CAB8 in Pisum sativum) and LHCAIII (light-harvesting chlorophyll-a/b protein of photosystem I, type III) that function as a light receptor to capture and deliver excitation energy to photosystems (Timko et al 1985), are among the genes most prominently overrepresented in the temperate plantlet transcriptome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations